2011
DOI: 10.1002/lt.22276
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of elderly donors in living donor liver transplantation: When more is less?

Abstract: An accepted definition of donor exclusion criteria has not been established for living donor liver transplantation (LDLT). The use of elderly donors to expand the living donor pool raises ethical concerns about donor safety. The aims of this study were (1) the comparison of the postoperative outcomes of living liver donors by age (!50 versus <50 years) and (2) the evaluation of the impact of the extent of right hepatectomy on donor outcomes. The study group included 150 donors who underwent donor right hepatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 41 publications
2
44
1
Order By: Relevance
“…A small liver remnant is the best predictor of hepatic dysfunction after liver resection. 22 Dayangac et al 11 reported that liver donation resulting in a remnant liver volume less than 35% should be avoided in donors 50 years or older to ensure their safety. Despite the conflicts inherent in ensuring both a sufficient GV for the recipient and a sufficient remnant liver volume for the donor, the safety of living donors should take priority in LDLT for elderly recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small liver remnant is the best predictor of hepatic dysfunction after liver resection. 22 Dayangac et al 11 reported that liver donation resulting in a remnant liver volume less than 35% should be avoided in donors 50 years or older to ensure their safety. Despite the conflicts inherent in ensuring both a sufficient GV for the recipient and a sufficient remnant liver volume for the donor, the safety of living donors should take priority in LDLT for elderly recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We used a cutoff of 50 years for the donor age because recipients of grafts from donors 50 years or older have a higher mortality rate and a lower 1-year survival rate than recipients of grafts from younger donors. 11 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is known that morbidity and mortality after hepatic resection for malignancy is strongly associated with volume of the future liver remnant [18]. It is likely that the smaller future liver remnant following right hepatic lobectomy contributes to the worse perioperative outcomes as echoed by many other studies involving living donors undergoing right hepatectomies [13,19,20]. Given the limitations of the ACS-NSQIP database we could not factor in the details on the size of future liver remnant or rates of post-hepatectomy liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our model only takes into consideration the donor, and not the recipient. There are factors such as age which affect the risks and complications, at least in a size dependent resection (Dayangac et al, 2011). We do not consider age given the few subjects we had, nor do we consider gender or ethnicity.…”
Section: Discussionmentioning
confidence: 99%